Knowledge, attitude, and use of protective measures against COVID-19 among nurses: a questionnaire-based multicenter cross-sectional study - Ramzi Shawahna (BMC, 2021)
Abstract Background During this pandemic, nurses have always been on the frontline and are probably the first healthcare providers to interact with patients presenting with symptoms of COVID-19. The main aim of this multicenter study was to assess knowledge, attitude, and use of protective measures against COVID-19 among nurses across the Occupied Palestinian Territory (oPt) during the ongoing pandemic. Methods This was a questionnaire-based multicenter cross-sectional study that was conducted in the period between October 2020 to December 2020. The study tool tested knowledge (8-item), attitude (2-item), and use of protective measures against COVID-19 (3-item) among nurses. Associations between nurses' characteristics and their knowledge, attitude, and use of protective measures were investigated using Student's t-test, Analysis of Variance, and Pearson's correlations. To control potentially confounding variables, predictors of higher knowledge, attitude, and use of protective measures were identified using multiple regression analyses. Results The study tool was complete by 455 nurses. The mean of knowledge, attitude, and use of protective measures scores were 75.7% (SD:12.4%), 75.1% (SD: 17.7%), and 91.6% (SD: 18.2%), respectively. Multiple linear regression models showed that high knowledge was predicted by being female (p-value = 0.004) and self-rating social status as high (p-value = 0.005). Higher attitude was predicted by being female (p-value = 0.005), self-rating academic achievements as high (p-value = 0.007), and having contracted COVID-19 (p-value = 0.001). Higher use of protective measures was predicted by self-rating academic achievements as high (p-value = 0.010). Conclusion Findings of this study suggested that nurses in the oPt had high knowledge, relatively optimistic attitude, and appropriately used protective measures against COVID-19 during the ongoing pandemic. Knowledge, attitude, and use of protective measures among nurses should continuously be updated as information unfold during the ongoing pandemic. More efforts are still needed to ensure protection of healthcare providers including nurses from contracting COVID-19.